Lysine‐Functionalized SnO2 for Efficient CO2 Electroreduction into Formate. Issue 5 (30th March 2022) - Lin, Chen; Xu, Zifan; Kong, Xiangdong; Zheng, Han; Geng, Zhigang; Zeng, Jie
Abstract: Electroreduction of CO2 to HCOO − can be considered as the most economically valuable process. Herein, we developed lysine‐functionalized SnO2 nanoparticles (SnO2 ‐lys) as an efficient catalyst for the electroreduction of CO2 into HCOO − . During CO2 electroreduction, SnO2 ‐lys achieved a Faradaic efficiency for HCOO − of higher than 80% over a wide range of applied potentials from −0.5 V to −2.3 V versus reversible hydrogen electrode ( vs . RHE). Notably, the partial current density for HCOO − reached as high as −351.9 mA cm −2 at −2.3 V vs . RHE. On account of kinetic analysis and mechanistic study, lysine‐functionalized SnO2 facilitated faradaic process and accelerated reaction kinetics via enhancing the CO2 activation, thus promoting the catalytic performance of the electroreduction of CO2 into HCOO − . Abstract : Lysine‐functionalized SnO2 nanoparticles (SnO2 ‐lys) were developed as an efficient catalyst for the electroreduction of CO2 into HCOO − . SnO2 ‐lys achieved a Faradaic efficiency for HCOO − of higher than 80% over a wide range of applied potentials with the highest ECSA‐normalized j of 63.8 mA cm −2 . Mechanistic studies revealed that the enhanced catalytic activity of HCOO − originated from the facilitated faradaic process and accelerated reaction kinetics due to the surface functionalization of lys.